Dasati enterprise: portable ceiling fan cleaner / Nur 'Ain Atiqah Mohd Yasin, Nur Hidayah Farhana Kamaruddin, Siti Nur Sarah Mohammad Zulkarnain - Mohd Yasin, Nur 'Ain Atiqah; Kamaruddin, Nur Hidayah Farhana; Mohammad Zulkarnain, Siti Nur Sarah (2017)
Entrepreneurship is a process innovation and new venture creation through four dimensions which includes individuals, organization, environment and institution. In order to form a business, there are quiet numbers of phase that should be understood and develops by entrepreneur.